RANCANG BANGUN ALAT UJI KELURUSAN BENDA BERBASIS ARDUINOUNO DENGAN MENGGUNAKAN SENSOR HC-SR04 - Naufal, Aziz Ibnu; Hadi M, Alaya Fadlu; Mrihardojhono, Juli (Jurnal Mekanova : Mekanikal, Inovasi dan Teknologi, 2022)
Design build Object Based Straightening Tools Arduino Uno Using HC-SR04 Sensor. Straightness test to be carried out so that the quality and quality of the product obtained is precise. By utilizing proximity sensor technology and Arduino Uno as a microcontroller, this is a solution to solve straightness test problems that still use conventional methods. Proximity sensor technology and Arduino Uno as a microcontroller are solution to detect the presence of objects in the vicinity without any physical touch. In the straightness test, the workpiece (pipe) is placed on the workpiece holder. The ultrasonic sensor will read how far the object is working with the ultrasonic sensor. The waves emitted by the ultrasonic sensor to the workpiece will be read back by the ultrasonic sensor to display data on the distance of the object to the sensor. The calibration method is carried out by using an inch pipe that has been confirmed to be straight, flat, and has no defects on its surface. The calibration process was carried out 10 times with a distance ranging from 10 mm – 100 mm. The function test of the measuring instrument is carried out after the calibration process is carried out and the test is carried out at a distance of 70 mm using 1 inch and 2 inch pipes. From the test data for 1 inch and 2 inch pipes, we get a table of error values from the measurements of the two pipes. The results of testing the prototype of this straightness test tool show that the prototype works effectively and efficiently, so that it can be applied in teaching and learning activities as well as in the industrial world.